From preliminary aircraft cabin design to cabin optimization - part 2 - Mihaela Niţă and Dieter Scholz (Scientific bulletin / University Politehnica of Bucharest = Buletin ştiinţific / Universitatea Politehnica din Bucureşti. Series D, Mechanical engineering, 2013)
This paper conducts an investigation towards main aircraft cabin parameters. The aim is two-fold: First, a handbook method is used to preliminarily design the aircraft cabin. Second, an objective function representing the "drag in the responsibility of the cabin" is created and optimized using both an analytical approach and a stochastic approach. Several methods for estimating wetted area and mass are investigated. The results provide optimum values for the fuselage slenderness parameter (fuselage length divided by fuselage diameter) for civil transport aircraft. For passenger aircraft, cabin surface area is of importance. The related optimum slenderness parameter should be about 10. Optimum slenderness parameters for freighters are lower: about 8 if transport volume is of importance and about 4 if frontal area for large items to be carried is of importance. These results are published in two parts. Part I includes the handbook method for preliminarily designing the aircraft cabin. Part II includes the results of the optimization and the investigations of the wetted areas, masses and "drag in the responsibility of the cabin".
Keywords: evolutionary algorithms; optimization; preliminary cabin design